Oil palm development in Buvuma - Learning from previous experiences and recommendations for future developments - Kiyingi, G.K.; Opige, M.; Ssemmanda, R.; Kisakye, J.; Wamala, P. (2020)
This synthesis paper informs the planned oil palm expansion in Buvuma. It draws on documented experiences from Uganda and especially Kalangala district, and highlighting the possible threats, pressures and impacts in Buvuma, and offering strategies and recommendations to mitigate these.